THE EFFECTIVNESS TEACHING READING COMPREHENSION USING GROUP WORK DISCUSSION METHOD - Astriliani Dadara; Sudiyono Sudiyono (IKIP Siliwangi, 2021)
This study aims at knowing how the effective teaching reading comprehension by using group work discussion method of the tenth grade students at SMKNPlered.The research design which is used in qualitative descriptive with one group. The subjects of this research were students from Industrial Automation Engineering 2 (TOI 2) of vocational high school Plered. The instruments used were interview, pre-test and post-test with the material recount text. From the reading skill test, the students’ pre-test mean score was 61.55 increasing to 81,89 in the post-test. So, it can be concluded that teaching reading by using group work discussion method an effective improve the students’ reading skill.